Why economic recovery is the slowest in Brazilian history? - Pires, Manoel Carlos; Borges, Bráulio; Borça Jr., Gilberto (Brazilian Keynesian Review, 2019)
Brazilian economic recovery that emerged from the 2014-16 recession is the slowest in history. Current low growth threats future growth reducing labor’s productivity and capital stock, which is widely known as hysteresis effect. Brazil has a large idleness, inflation below the target and both must result in lower interest rate. Monetary stimulus will improve economic activity and create space for fiscal policy and other themes of economic policy debate.